Infectious bronchitis virus replication in the chicken embryo related cell line - Ferreira, H. L.; Pilz, D.; Mesquita, L. G.; Cardoso, T. (Carfax Publishing, 2003)
The susceptibility of the chicken embryo related (CER) cell line to infectious bronchitis virus (IBV M41) was characterized after five consecutive passages in CER cells. Virus replication was monitored by cytopathic effect observation, electron microscopy, indirect immunofluorescence, and reverse transcription polymerase chain reaction (RT-PCR). At 96 h post-infection (p.i.), the cytopathic effect was graded 75% by cell fusion, rounding up of cells and monolayer detachment, and the electron microscopy image characterized by coronavirus morphology. Cytoplasmic fluorescence was readily observed by from 24 h p.i. onwards, and at all times the respective viral RNA from IBV-infected monolayers was demonstrated by RT-PCR. Extra-cellular virus was measured by virus titration performed on chicken kidney cells and embryonated chicken eggs, and respective titres ranged from 4.0 to 6.0 log(10) EID50/ml on embryonated chicken eggs, and from 2.0 to 6.0 log(10) TCID50/ml on both CER cells and chicken kidney cells studied from 24 to 120 h p.i. These results confirmed that the M41 strain replicated well in the CER cell line.